Respiratory pathogen spectrum and epidemiological trends in Hainan Province: a retrospective analysis from 2017 to 2023 - Lvying Wu; Jianan Zhang; Zhiming Wu; Hua Pei; You Zhang (BMC Infectious Diseases)
Abstract Background Respiratory tract infections (RTIs) pose a significant global health burden, caused by various pathogens. The COVID-19 pandemic and non-pharmaceutical interventions (NPIs) have created unprecedented challenges for public health systems, inadvertently altering the dynamics of other respiratory pathogens. This study aims to illustrate changes in the pathogen spectrum among RTI patients in Hainan Province before and during the pandemic. Methods A retrospective study was conducted to demonstrated the epidemiology characteristics of respiratory pathogens across pre-COVID-19, NPI and COVID-19 pandemic in Hainan from 2017 to 2023. A total of 21,036 patients with RTI of all age groups were enrolled and tested for nine common pathogens: influenza A virus (Flu-A), influenza B virus (Flu-B), parainfluenza virus (PIV), Adenovirus (AAV), respiratory syncytial virus (RSV), Q fever Rickettsiae (Q Fever), Legionella pneumophila (L. pne), Chlamydia pneumoniae (C. pne), and Mycoplasma pneumoniae (M. pne). Results During 2017–2023, the number of RTI patients and pathogen detection rate was gradually decrease from 33.30% (3,886/11,670; pre-COVID-19), to 30.81% (2,034/6,602; NPI) and 22.43% (620/2,764; COVID-19). M. pne (25.52%), Flu-B (3.9%), and PIV (3.12%) were identified as the most prevalent pathogens across three periods. However, the infection rate for M. pne was significantly decrease, and the infection rate for Flu-B and Flu-A were a notable increased in NPI and COVID-19 pandemic. Children aged 0–5 years account for the largest proportion of all RTI patients with the highest infection rate, especially in NPI and COVID-19 pandemic. Flu-A, Flu-B, and RSV exhibited spring-specific seasonal prevalence during NPI and COVID-19 pandemic. Co-infection pattern analysis showed that “M. pne-dominant viruses” co-infection type was prevalent across all three time periods. Conclusion M. pne, Flu-B, Flu-A, and PIV were found to be the main causative pathogens of RTI patients in Hainan Province, and their prevalence levels and seasonal patterns had changed during large-scale NPI and COVID-19 pandemic.